2019
DOI: 10.3389/fphys.2019.00423
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Genes in the Metabolism of Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common disease, which is characterized by the accumulation of triglycerides in the hepatocytes without excess alcohol intake. Circadian rhythms can participate in lipid, glucose, and cholesterol metabolism and are closely related to metabolism seen in this disease. Circadian clock genes can modulate liver lipid metabolism. Desynchrony of circadian rhythms and the influences imparted by external environmental stimuli can increase morbidity. By contrast, synchronizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 81 publications
(82 reference statements)
0
49
0
Order By: Relevance
“…For example, previous studies showed that clock genes have demonstrated a role of circadian rhythm in muscle atrophy and bone remodeling [ 53 , 54 , 55 ]. In addition, these clock genes have been implicated in NAFLD [ 56 ], the symptoms of which have been observed in mice during spaceflight [ 10 ]. Furthermore, Arntl plays a role in the circadian regulation of acute glucocorticoid secretion in the adrenal glands in response to stress [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies showed that clock genes have demonstrated a role of circadian rhythm in muscle atrophy and bone remodeling [ 53 , 54 , 55 ]. In addition, these clock genes have been implicated in NAFLD [ 56 ], the symptoms of which have been observed in mice during spaceflight [ 10 ]. Furthermore, Arntl plays a role in the circadian regulation of acute glucocorticoid secretion in the adrenal glands in response to stress [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…We know that genetics, heritability, and gender type are major factors that raise the susceptibility to develop T2DM, IR, NAFLD, obesity, and/or other metabolic syndromes [133,134]. While these cannot be changed, factors such as the circadian rhythm that interestingly promotes metabolic disruptions [135,136], lifestyle (exercise, weight loss), and dietary changes can improve clinical and paraclinical outcomes of NAFLD and T2DM on long term [137,138]. More than that, continuous exposure to environmental factors like endocrine-disrupting chemicals such as the ubiquitous phthalates and heavy metals adversely affect human health.…”
Section: Dietary and Lifestylementioning
confidence: 99%
“…Microbiota rhythms are regulated by diet and time of feeding which can alter both microbial community structure and metabolic activity that can significantly impact metabolic function [99]. Indeed, an increasing number of circadian rhythm studies have provided important insights correlating the expression of the circadian clock gene with metabolism in NAFLD [100]. However, the exact mechanisms of circadian metabolism remain obscure and unresolved at this time, and clearly require additional experimentation to further increase our comprehension of lipid metabolism in the liver.…”
Section: Future Perspectivesmentioning
confidence: 99%